Consumption Values and Smartphone Choice in Taiwan and China - Lo, Ai Wei (2013)
The purpose of this research is to discover which consumption values differentiate between domestic smartphone users and foreign smartphone users and the correlation between smartphone consumption choice and demographic characteristics in Taiwan and China respectively. Besides, a cross-cultural comparison is made. This research used 457 respondents as samples. A self-developed consumption values survey based on Sheth-Newman-Gross model (1991) is conducted. The findings regarding consumers in Taiwan revealed that demographic characteristics have little to do with smartphone choice and functional value plays the most important role in influencing smartphone choice. On the other hand, social value and epistemic value are two salient consumption values that drive people to choose foreign smartphone over domestic smartphone in China. Besides, male consumers and consumers with higher educational attainment possess a higher tendency to buy foreign smartphone than domestic smartphone. To bring to an end, difference in scoring the importance of each consumption value between Taiwan and China has detected and demonstrated.